Links between short-chain fatty acids and osteoarthritis from pathology to clinic via gut-joint axis - Juanjuan Han; Xin Meng; Hui Kong; Xinran Li; Peijie Chen; Xin-an Zhang (Stem Cell Research & Therapy)
Abstract Short-chain fatty acids (SCFAs), the primary metabolites produced by the microbial fermentation of dietary fibers in the gut, have a key role in protecting gut health. Increasing evidence indicates SCFAs can exert effects on distant tissues and organs beyond the gut via blood circulation. Osteoarthritis (OA) is a chronic inflammatory joint disease that severely diminishes the physical function and quality of life. However, effective clinical treatments for OA remain elusive. Recent studies have shown that SCFAs can exert beneficial effects on damaged joints in OA. SCFAs can mitigate OA progression by preserving intestinal barrier function and maintaining the integrity of cartilage and subchondral bone, suggesting that they have substantial potential to be the adjunctive treatment strategy for OA. This review described the SCFAs in the human body and their cellular signaling mechanism, and summarized the multiple effects of SCFAs (especially butyrate, propionate, and acetate) on the prevention and treatment of OA by regulating the gut-joint axis, providing novel insights into their promising clinical applications.